2022
DOI: 10.3390/ijms23095095
|View full text |Cite
|
Sign up to set email alerts
|

Actin Stress Fibers Response and Adaptation under Stretch

Abstract: One of the many effects of soft tissues under mechanical solicitation in the cellular damage produced by highly localized strain. Here, we study the response of peripheral stress fibers (SFs) to external stretch in mammalian cells, plated onto deformable micropatterned substrates. A local fluorescence analysis reveals that an adaptation response is observed at the vicinity of the focal adhesion sites (FAs) due to its mechanosensor function. The response depends on the type of mechanical stress, from a Maxwell-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…84 Thus efforts are concentrated on studying how cells respond to mechanical stimuli so materials can be made to limit potential or irreversible cell damage. 85–87 When preparing materials, Younes et al confirmed the effects of crosslinking density of biocompatible polycaprolactone based star-copolymer elastomer and the stress of the material. 50 We reported that with the incorporation of the LC pendants, the liquid crystalline character of the LCE made it more resistant to strain, however it was still able to mimic the properties of tissue elasticity.…”
Section: Liquid Crystal Elastomers As Biomaterialsmentioning
confidence: 99%
“…84 Thus efforts are concentrated on studying how cells respond to mechanical stimuli so materials can be made to limit potential or irreversible cell damage. 85–87 When preparing materials, Younes et al confirmed the effects of crosslinking density of biocompatible polycaprolactone based star-copolymer elastomer and the stress of the material. 50 We reported that with the incorporation of the LC pendants, the liquid crystalline character of the LCE made it more resistant to strain, however it was still able to mimic the properties of tissue elasticity.…”
Section: Liquid Crystal Elastomers As Biomaterialsmentioning
confidence: 99%